DOES THE NATURE OF INTERACTIONS WITH HIGHER EDUCATION INSTITUTIONS INFLUENCE THE INNOVATIVE CAPABILITIES OF CREATIVE FIRMS? THE CASE OF A SOUTHWESTERN NORWEGIAN COUNTY - Calignano, Giuseppe; Jøsendal, Kari (Quaestiones Geographicae, 2018)
Our study contributes to a limited body of literature and aims to examine the type and frequency of linkages between creative industries and higher education institutions (HEIs). The objective of our study is to investigate the extent to which various types of linkages contribute to enhanced innovative capabilities in creative industries. Based on a qualitative research design and a case study carried out in a peripheral south-western Norwegian county, our empirical analysis shows that HEIs are generally not very relevant partners and that other actors are mainly involved in innovation dynamics. As clarified and discussed in the paper, this finding largely depends on some specific characteristics of HEIs, the form of knowledge primarily employed by creative firms (symbolic knowledge base), and the cultural divergence between the two spheres.